Compact Oxford dictionary, thesaurus, and wordpower guide - edited by Sara Hawker (Oxford University Press, 2006)
The Compact Oxford Dictionary, Thesaurus, and Wordpower Guide is a brand-new three-in-one reference from Oxford. With a clear colour design, it gives easy access to essential everyday vocabulary for all your writing needs. Use the dictionary to check spellings and meanings. Thousands of up-to-date words, phrases, and definitions are given in a clear and simple style, making them easy to understand. Hundreds of notes on spelling and grammar help you get it right. Use the thesaurus to broaden your vocabulary and improve your writing skills. There are thousands of alternative and opposite words, with the most useful synonym given first for ease of use. Thousands of real examples of usage show synonyms in context and help you identify the correct sense